2000
DOI: 10.1034/j.1600-0749.2000.130109.x
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Cutaneous Melanomas in Camargue‐Type Gray‐Skinned Horses (2): Epidemiological Survey

Abstract: An epidemiological survey was made on cutaneous melanomas occurring in Camargue-type, gray-skinned horses in southern France. The population investigated was composed of 264 horses, which were selected from the Camargue horse stud registry and were allowed to be examined by the owners. The presence of tumors was inspected macroscopically according to the standardized protocols of veterinary medicine specialists, and some tumors were subjected to macroscopic histopathological examination. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 2 publications
7
40
0
5
Order By: Relevance
“…1268, 2012 A maioria dos tumores melanocíticos inicia-se na região ventral da cauda, no períneo e na genitália externa e, menos comumente, na glândula parótida, na orelha, na pálpebra, nos membros e no pescoço. Após transformação maligna, a formação de metástases ocorre via hematogênica, linfática ou por implantação, e os principais locais envolvidos são linfonodos regionais, baço, fígado, pulmões, vasos sanguíneos e coração (FLEURY et al, 2000;JOHNSON, 1998;MACGILLIVRAY;SWEENEY;PIERO, 2002).…”
Section: Introductionunclassified
“…1268, 2012 A maioria dos tumores melanocíticos inicia-se na região ventral da cauda, no períneo e na genitália externa e, menos comumente, na glândula parótida, na orelha, na pálpebra, nos membros e no pescoço. Após transformação maligna, a formação de metástases ocorre via hematogênica, linfática ou por implantação, e os principais locais envolvidos são linfonodos regionais, baço, fígado, pulmões, vasos sanguíneos e coração (FLEURY et al, 2000;JOHNSON, 1998;MACGILLIVRAY;SWEENEY;PIERO, 2002).…”
Section: Introductionunclassified
“…O neoplasma aqui relatado foi classificado como melanoma maligno anaplásico (VALENTINE, 1995). Estudos indicam que a maioria dos neoplasmas melanocíticos inicia-se na região ventral da cauda, no períneo e na genitália externa e, menos comumente, na glândula parótida, na orelha, na pálpebra, nos membros e no pescoço (FLEURY et al, 2000;MACGILLIVRAY et al, 2002). Após transformação maligna, a formação de metástases ocorre via hematogênica, linfática ou por implantação, e os principais locais envolvidos são linfonodos regionais, baço, fígado, pulmões, vasos sanguíneos e coração (JOHNSON, 1998;MACGILLIVRAY et al, 2002).…”
unclassified
“…Sundberg et al (1977) reported higher frequencies of melanoma occurrence in males. Fleury et al (2000b) recorded a higher melanoma occurrence in geldings compared to mares and stallions but the differences were on the boundary of statistical significance. The other authors are also convinced that sex does not influence the occurrence of melanoma (e.g.…”
Section: Analysis Of Environmental Effectsmentioning
confidence: 95%